2013
DOI: 10.1007/s40279-013-0103-4
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical and Physiological Demands of Kitesurfing and Epidemiology of Injury Among Kitesurfers

Abstract: Kitesurfing is a relatively new extreme water sport that is considered a high-risk sport and has rising popularity. Kitesurfing combines aspects of several water sports, including surfing, windsurfing, and wakeboarding. With a large controllable kite and a small board, kitesurfers travel over the water surface with speeds of up to 35 knots. The vertical lift of the kite makes it possible to perform jumps up to 15 m high and 30 m long, while doing different manoeuvres in the air. Few scientific data are availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 32 publications
2
39
0
4
Order By: Relevance
“…A review of the literature identified an overall injury rate of 5.9 to 7.0 injuries per 1000 noncompetitive kitesurfing hours[12]. A prospective kitesurf study showed an injury rate of 7 injuries per 1000 h of practicing the sport[9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the literature identified an overall injury rate of 5.9 to 7.0 injuries per 1000 noncompetitive kitesurfing hours[12]. A prospective kitesurf study showed an injury rate of 7 injuries per 1000 h of practicing the sport[9].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increasing popularity and possible dangers of this sport, little is known about injury prevalence or prevention[8]. However, some reports did analyse kitesurfing injuries and even reported fatal accidents[9-12]. …”
Section: Introductionmentioning
confidence: 99%
“…It is a high-risk activity that combines several water sports including surfing, windsurfing and wakeboarding 2. Using a large kite and small fibreglass board, travel occurs by opposing the force of the wind through tension on a string.…”
Section: Introductionmentioning
confidence: 99%
“…The apparatus consists of a large controllable kite with a handlebar connected to the kite surfer's harness, and a small board with footpads and straps for riding over the water; athletes are pulled over the water surface, performing jumps and several risky elements in the air even in conditions of light wind (Bourgois et al 2014;Nebas & Heller 2014). A kitesurfing competition can be performed in two main categories in accordance with the type of elements involved -namely, crossing (sideways transportation over the surface of the water) and freestyle (jumps and pop tricks) (Bourgois 2014). The few scientific data suggest that crossing is sustained by aerobic metabolism and is of a moderately intense activity (65-70% VO 2 max) (Vercruyssen et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The few scientific data available concern: biomechanical (Bourgois et al 2014) and physiological aspects (Vercruyssen et al 2009;Camps et al 2011;Clua et al 2014); comfort and safety of the equipment design (lundgren et al 2012;Nebas & Heller 2014); and injuries sustained (lundgren et al 2012;Driessen et al 2015).…”
Section: Introductionmentioning
confidence: 99%